Analisis Kadar Logam Kadmium (Cd) dan Timbal (Pb) pada Sedimen Di Teluk Ambon Bagian Dalam - Male, Yusthinus T; Malle, Dominggus; Bijang, Catherina Manukpadang; Fransina, Eirene Grace; Seumahu, Cecelia Anna; Dolaitery, Lois Mikhal; Landu, Sartika; Gaspersz, Nelson (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2017)
The research about analysis of cadmium (Cd) and lead (Pb) metal content on sediment inner part of Ambon Bay has been done. Sampling point located at Dermaga Ferry Poka, PLTD Poka, Kate-kate, Waiheru, Lateri III, Passo dan PLTD Galala. The results of analyzed of sediment particle size inside the Ambon Bay showed 3 components were sand, gravel, and sludge, but the sediments was dominated by sludge sand. Analysis of Cd content showed that at 7 stations in Ambon Bay detected Cd metal with the highest concentration at 4th station of Waiheru village was 0,6640 mg/Kg and the lowest concentration at 3th station of Kate-kate village was 0,0980 mg/Kg. Meanwhile, the highest Pb content was 20,075 mg/kg at 4th station and the lowest was 5,755 mg/kg at 2nd station of PLN Poka. The content of elements composition of sediment are SiO2, K2O, P2O5, Fe2, BaO, NiO and Ga2O3 but Cd and Pb metal was not detected.